Analisis Teknologi Manajemen Energi Pada Kendaraan Listrik Hibrida Berbasis Tinjauan Pustaka - Theophilus Ezra Nugroho Pandin; Bryan Hulio Santoso; Rasional Sitepu; Andrew Joewono (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2022)
The application of hybrid electric vehicle technology has grown rapidly in recent years. This article aims to describe and discuss energy management strategies in hybrid electric vehicles. The research method is qualitative with a systematic literature review based on database searches on IEEE, Garuda SINTA, ArXiv, Preprints. The results obtained 13 articles from the IEEE database by describing the results of the energy management strategy of each article. The conclusion is that the technology used for energy management strategies includes algorithm settings, namely reinforcement learning and Q-learning combined with several control systems, namely predictive control models, Equivalent Consumption Minimization Strategy, and Dynamic Programming.